Potensi Ekstrak Daun Binahong (Anredera cordifolia) Sebagai Penghambat Bakteri Vibrio harveyi - Kartika, Gde Raka Angga; Andayani, Sri; Soelistyowati, Soelistyowati (Journal of Marine and Aquatic Sciences; Vol 2 No 2 (2016), 2016)
Binahong ( Anredera cordifolia ) is a plant that can treat various kinds of diseases, because this plant has a high antioxidant content and as an antibacterial and antiviral. Vibriosis disease caused by the bacterium Vibrio harveyi is a serious problem in marine and brackish culture, this disease can cause death for shrimp and fish that farmed in marine or brackish. This study aims to determine the potential of using leaf extract Binahong with different concentrations as Vibrio harveyi inhibiting bacterial growth in vitro. The method used is to test the Minimum inhibitory concentration (MIC) to determine minimum levels inhibit the growth of Vibrio harveyi and Minimum Bactericidal Concentration (MBC) using paper disc. The results showed the use of leaf extract Binahong ( Anredera cordifolia ) with different concentrations significant effect on the growth of Vibrio harveyi in vitro. Binahong leaf extract ( Anredera cordifolia ) with a concentration of 3%, 5%, 7%, 9%, 11% and 13% is only bacteriostatic which inhibits the growth of bacteria Vibrio harveyi with the best concentration obtained is equal to 13%.
Keywords: Binahong leaves; Vibrio harveyi; inhibition